Picosecond control of quantum dot laser emission by coherent phonons - Czerniuk, T.; Wigger, D.; Akimov, A.V.; Schneider, C.; Kamp, M.; Höfling, S.; Yakovlev, D.R.; Kuhn, T.; Reiter, D.E.; Bayer, M. (American Physical Society, 2017)
A picosecond acoustic pulse can be used to control the lasing emission from semiconductor nanostructures by shifting their electronic transitions. When the active medium, here an ensemble of (In,Ga)As quantum dots, is shifted into or out of resonance with the cavity mode, a large enhancement or suppression of the lasing emission can dynamically be achieved. Most interesting, even in the case when gain medium and cavity mode are in resonance, we observe an enhancement of the lasing due to shaking by coherent phonons. In order to understand the interactions of the nonlinearly coupled photon-exciton-phonon subsystems, we develop a semiclassical model and find an excellent agreement between theory and experiment.